(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2008)
The present paper is the second in a series devoted to the revision of the Pliocene naticids of Northern and Central Italy. It concludes the section covering the calcareous operculum-bearing Naticinae and expands to 18 the total number of species and subspecies of this subfamily recovered so far from the Pliocene deposits of Italy. Of the six taxa considered in this study, two (epigloafuniculata and fredianii) fully match the characters of the genus Cochlis Röding, 1798, one (koeneni) is assigned to the genus Tanea Marwick, 1931, the rest (astensis, prietoi and tectula) belong to the genus Tectonatica Sacco, 1890. All the six taxa considered in this paper are described and commented in the systematic account. One, Cochlis fredianii, is proposed as new. In the chapter treating the generic assignment of the studied taxa, the range of Tanea, hitherto used to allocate several Indo-Pacific species, is extended to the Mediterranean Basin as well, and the relations between Tectonatica and Cryptonatica Dall, 1892 are discussed. This study further demonstrates that the morphological characters of the teleoconch are of low significance in species recognition. In fact, should the characters be ranked, the operculum comes first and is the primary element, sufficient to distinguish each species. The protoconch and the color pattern are the second and third relevant attributes that can be used diagnostically for several taxa, but not always. The other shell features appear to be useful tools in separating species only occasionally. Some species lack distinctive shell characters and do require operculate specimens in order to be confidently